Pengaruh Model Pembelajaran Classroom Meeting terhadap Keaktifan Belajar Peserta Didik pada Mata Pelajaran PAI Fase E - Salamudin, Ceceng; Amwaliah, Agnia (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
This research is based on the still low level of student participation in classroom learning. One model that can enhance student participation is the Classroom Meeting Learning Model. However, initial observations revealed that the percentage of student learning activity was still below 50%. This was evident from students' inability to present their work, participate in tasks, and ask questions to peers or educators when they did not understand the issues they were facing during the Classroom Meeting learning model. The purpose of this study is to describe: 1) the Classroom Meeting learning model in Islamic Education (PAI) Phase E; 2) the student learning activity in Islamic Education (PAI) Phase E; and 3) the impact of the Classroom Meeting learning model on student learning activity in Islamic Education (PAI) Phase E at SMA IT At-Ta'awun Sukaresmi Garut. This study was conducted over a period of three months. This research uses a quantitative approach with a descriptive method. Data collection was done through observation, documentation study, and a questionnaire filled out by 31 students who were the samples in this study, while data processing was done through statistical data analysis using linear regression. Based on the results of the data analysis regarding the Classroom Meeting learning model, the average score obtained was 4, which falls into the "Very Good" category. This indicates that the Classroom Meeting learning model has an impact on student learning activity. Meanwhile, based on the analysis of student learning activity data, the average score obtained was 3.90, which falls into the "High" category. This shows that the application of this model is an appropriate solution to enhance student learning activity. According to statistical tests, there is an effect of the Classroom Meeting learning model on student learning activity, accounting for 29.7%, which is categorized as "Low", while other factors influencing student learning activity account for 70.3%, but were not examined in this study.  Keywords: classroom meeting learning model, learning engagement, islamic religious education.